2014
DOI: 10.1155/2014/654712
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAntiviral Activity of Circular Triple Helix Forming Oligonucleotide RNA towards Feline Infectious Peritonitis Virus Replication

Abstract: Feline Infectious Peritonitis (FIP) is a severe fatal immune-augmented disease in cat population. It is caused by FIP virus (FIPV), a virulent mutant strain of Feline Enteric Coronavirus (FECV). Current treatments and prophylactics are not effective. The in vitro antiviral properties of five circular Triple-Helix Forming Oligonucleotide (TFO) RNAs (TFO1 to TFO5), which target the different regions of virulent feline coronavirus (FCoV) strain FIPV WSU 79-1146 genome, were tested in FIPV-infected Crandell-Rees F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(37 reference statements)
0
9
0
1
Order By: Relevance
“…However, this cat showed neurological manifestations and was euthanised due to status epilepticus after 38 days of treatment [73]. Moreover, other agents have also been shown to have in vitro antiviral activity against FCoV, including an anti-feline TNF-alpha monoclonal antibody [16]; U18666A (a cholesterol transport inhibitor) [18,74]; diphyllin (a vacuolar ATPase blocker) and its nanoformulation [17] and a circular triple helix forming oligonucleotide RNA [15]. However, no in vivo studies have been reported using these compounds.…”
Section: Other Antiviral Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this cat showed neurological manifestations and was euthanised due to status epilepticus after 38 days of treatment [73]. Moreover, other agents have also been shown to have in vitro antiviral activity against FCoV, including an anti-feline TNF-alpha monoclonal antibody [16]; U18666A (a cholesterol transport inhibitor) [18,74]; diphyllin (a vacuolar ATPase blocker) and its nanoformulation [17] and a circular triple helix forming oligonucleotide RNA [15]. However, no in vivo studies have been reported using these compounds.…”
Section: Other Antiviral Compoundsmentioning
confidence: 99%
“…In reviewing treatment options for FIP, numerous older studies describing potential treatments are mostly based on cases without a confirmed diagnosis of FIP and hampered by the lack of well-controlled clinical trials [14]. Likewise, the use of other reported treatment options is currently only supported by in vitro studies rather than through in vivo clinical studies [15,16,17,18]. Despite recent antiviral studies with GC376 and GS-441524 showing great promise against FIPV in naturally and experimentally infected cats [19,20,21], these agents have not yet obtained registration for veterinary use [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bai et al used CpG ON as vaccine additive to treat Hepatitis B, due to its ability to promote binding capacity of naïve B cells to the Hepatitis B virus epitopes [ 46 ]; Triple-helix-forming ON is formed by single strand ON inserting into the double stranded DNA. After the insertion, double stranded DNA can’t transcribe mRNA and therefore relevant protein expression is inhibited [ 47 ].…”
Section: Mechanism Of Action and Major Application Of On Drugsmentioning
confidence: 99%
“…cDNA was synthesized using the SensiFAST™ cDNA Kit (Bioline, UK), as instructed by the manufacturer. Virus quantification was performed using SYBR Green-based real-time PCR as described previously with a slight modification [25]. Briefly, quantitative real-time PCR (qPCR) was performed in a 20 μl reaction consisting of 1 μl cDNA, 1 μl forward primer (1 μmol), 1 μl reverse primer (1 μmol), 7 μl nuclease-free water and 10 μl 2× SensiFAST SYBR® No-ROX mix (Bioline, UK).…”
Section: Detection Of Viral Load By Sybr Green-based Real-time Pcrmentioning
confidence: 99%